Sustainable economic goals based on determinants of resource productivity in the Netherlands and Hungary - Botond Géza Kálmán; Laszlo Vasa; Szilárd Malatyinszki (Environmental Economics)
Resource productivity has become an important indicator of sustainable economic growth in a situation when natural resources are becoming scarce and environmental stress is growing. This paper examines the drivers of resource productivity in the case of the Netherlands and Hungary, two countries featuring diversified economies and contexts. This paper evaluates the contribution of waste management, renewable energy sources, human capital, investment, and innovation to sustainability by adopting a combined methods approach. Data from Eurostat and ODYSSEE databases, covering the period from 2011 to 2021, were analyzed using time series comparison and structural equation modeling (SEM). The results indicate that factors such as employment rate, gross fixed capital formation (GFCF), waste recycling, and renewable energy significantly influence resource productivity. The results indicated absolute decoupling for the Netherlands, represented by a 40% increase in productivity with an 11% reduction in materials. In comparison, Hungary recorded relative decoupling with GDP and material consumption increasing by about 49% and 37%, respectively. These findings underpin the importance of tailored policies for the enhancement of resource efficiency and sustainable development.